2023
DOI: 10.1042/bsr20212791
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing FDA-approved drugs as FXR agonists: a structure basedin silicopharmacological study

Abstract: Farnesoid X receptor (FXR) modulates the expression of genes involved in lipid and carbohydrate homeostasis and inflammatory processes. This nuclear receptor is likely a tumor suppressor in several cancers but its molecular mechanism of suppression is still under study. Several studies reported that FXR agonism increase the survival of colorectal, biliary tract and liver cancer patients. In addition, FXR expression was shown to be downregulated in many diseases such as obesity, irritable bowel syndrome, glomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 105 publications
1
2
0
Order By: Relevance
“…And there were no signi cant conformational changes in CYP3A4 and CYP7A1 upon binding with OCA. Notably, the binding energy of OCA-FXR (-7.63 kcal/mol) closely aligns with the previously reported value of -7.6 kcal/mol [40]. Zhang et al observed that OCA improved the hepatic bile acid pro les induced by lipopolysaccharide in pregnant mice, accompanied by the lower expression of bile acid synthase CYP7A1 and the higher expression of CYP3A [41], which was similar to our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…And there were no signi cant conformational changes in CYP3A4 and CYP7A1 upon binding with OCA. Notably, the binding energy of OCA-FXR (-7.63 kcal/mol) closely aligns with the previously reported value of -7.6 kcal/mol [40]. Zhang et al observed that OCA improved the hepatic bile acid pro les induced by lipopolysaccharide in pregnant mice, accompanied by the lower expression of bile acid synthase CYP7A1 and the higher expression of CYP3A [41], which was similar to our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is still a long journey ahead. The optimization of concentrations of the compounds, the evaluation of the long-term effects, and the discovery of novel FXR agonists by repurposing FDA-approved drugs might be a promising approach for effectively targeting FXR in cancer [ 216 ]. Considering the fact that FXR and TGR5 are well-characterized receptors of BAs, the application of the dual FXR/TGR5 ligand might be superior to the use of a single agonist [ 217 ].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…This makes BAs receptors a target for the treatment of liver diseases such as cholestasis, viral hepatitis, liver fibrosis and liver cancer. At present, the FXR agonist obeticholic acid phase III clinical trial results have significant efficacy, and other FXR agonists such as GSK2324 and WAY-362450 have also entered clinical trials and achieved good clinical results (33). Targets for TGR5 are also expected to enter clinical trials in the near future.…”
Section: Regulations Of Bas In Hccmentioning
confidence: 99%